The Resilience of the Vulnerable Minority English Education Sector During the COVID-19 Pandemic - Advisory Board on English Education (2023)
This brief describes the vulnerabilities experienced in Québec’s English education sector, specifically in elementary and secondary schools and adult education and vocational training centres. The brief’s findings and recommendations are derived from a review of the research and from a survey conducted by ABEE. This survey (see Appendix 1) focused on the six vulnerable areas identified in the CSE report: mental health and well-being; teaching, learning and evaluation; professional development and training; governance and administration; education funding and resources; access and equity. The survey was made available in both French and English and sent to English sector teachers, administrators, parents and students. A detailed analysis of its findings is available in this brief's Research, Findings and Analysis section.

A Public Transportation Renaissance in a Post-Pandemic Context - Gherman, Stefan (2023)

2022-2023 Activity Report - Literacy Quebec (LQ) (2023)

Resolution 2023-05 : Address the Impact of COVID on Student Learning - Quebec Federation of Home and School Associations (QFHSA) (2023)
Parallel title : Resolutions Adopted at the 2023 Annual General Meeting

2021-2022 Annual Report : Saint Brigid's Home Residents' Committee - King, Kerry-Anne (Jeffery Hale - Saint Brigid's (JHSB), 2022)

[Jeffery Hale - Saint Brigid’s Users’ Committee Annual Report: 2021-2022] - Jeffery Hale – Saint Brigid’s Users’ Committee (Jeffery Hale - Saint Brigids (JHSB), 2022)
The Jeffery Hale-St. Brigid’s Users’ Committee met ten times from April 2021 to March, 2022 plus at the Annual Meeting on June 7, 2021. There were no in-person meetings held because of the Public Health constraints imposed by the COVID 19 worldwide pandemic so all meetings were held through Zoom. Some of the main challenges this public health situation has presented to the Committee have been the difficulty of meaningfully supporting staff in both residences, limited in- person access to Residents and their families, recruiting new members, and the complications in planning and implementing programmes.
issued: 2021/2022

Report on the Education and Vitality Forum : Overview - Macris, Antonia; QUESCREN (2022)

Sense of Belonging Among English-speaking Youth in Québec : Confronting Isolation Through Digital Community Building - Pettem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2022)
Since the onset of Covid-19, community has come to inhabit a digital medium for many of Québec’s English-speaking youth. But what does this mean in concrete terms? How is this linguistic minority using social media, and in what manner are they experiencing this digital shift? Will they want to keep having online events going forward? Our paper observes the digital behavior of young (aged 16-30) English-speaking Québecers from March 2020 until the current moment in the pandemic’s development.

Newsletter - English Parents' Committee Association (EPCA) (2022)
Number of pages: 11

Partners in Health - Centre for Access to Services in English (CASE) (2022)
Number of pages: 5

The Effects of the Pandemic on the Arts & Creative Sector in Québec : How Anglophone Artists, Creators, and Performers are Faring in a Time of Adversity - Eraso, Cecilia (Youth for Youth Québec (Y4Y Québec), 2022)
The arts, entertainment, and recreation sector is infamous for being in a state of constant flux. The experience of consecutive short-term contracts and annual seasonal employment terminations is a familiar reality for many creators, producers, and performers in Québec (Jeannotte, 2021). What is unique for some Québec artists is the experience of a linguistic divide in the provincial arts sector. In 2016, English-speaking artists in the province earned less than their Francophone counterparts, on average, making a median income of “85 cents for every $1 made by Francophone artists’’ (Hill, 2020). On the national level, statistics from the 2016 Canadian Census show that Anglophone artists from Québec have a lower median income than the rest of Canadian artists. These findings are especially surprising when considering that, nationally, English-speakers in Québec represent a significant portion of Canadian artists. Anglophones in Québec account for 4.6% of all Canadian artists, despite only representing 2.8% of the Canadian labour force (Hill, 2020). The data indicate that two factors, occupation and language, are related to discrepancies in income levels in Québec.

COVID-19 Update - Quebec Drama Federation (QDF) (2022)

A New Confinement That Will Leave Its Mark - Morse, Rachel; Régnier, Laurence (2022)

January 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 3

Impact Report 2021-2022 - 4Korners (2022)

ArtistsInspire Grants COVID-19 Protocol - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

Lunch & Learn : Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada: un état des lieux / Understanding the Long-Term Care Experience of Official Language Minorities in Canada : An Environmental Scan - Ménard, Alixe; Scott, Mary; Hsu, Amy (2022)

2021-2022 Annual Report - The English Speaking Catholic Council (2022)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 13

Partners in Health - Centre for Access to Services in English (CASE) (2021)
Number of pages: 5

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 19

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

Partners in Health - Centre for Access to Services in English (CASE) (2021)
Number of pages: 5

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 18

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 15

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 8

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

Partners in Health - Centre for Access to Services in English (CASE) (2021)
Number of pages: 3

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 10

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

COVID-19 Survey Report II - Literacy Quebec (LQ) (2021)
While the pandemic has forced a lot of swift changes, the majority of Literacy Quebec's member organizations have been able to adapt. In fact, 8 out of 9 respondents claimed to have successfully transitioned at least some of their programs and services online. However, while most organizations were able to move to some type of online- learning model, a select few reported having no available tutors/volunteers. Some of the reasons ranged from a lack of interest (i.e. volunteers originally signed up to interact with others in person), or a lack of confidence in using technology.

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 14

Did the Black Lives Matter Movement Help English-speaking Black Young Adults in Quebec Recover from the Damaging Psychological Effects of the COVID-19 Pandemic? - Koestner, Richard; Holding, Anne C. (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The historic events of the spring of 2020—the collision of the worst public health crisis in a century and the largest Black civil rights movement in half a century—offer a unique opportunity to examine how the frustrations and hopes of English-speaking Black young adults were affected. We sought to understand the potentially competing impacts that the public health and social justice crises have had on the young adults in their communities. Quebec has the second largest Black population in Canada (after Ontario), with 27% of Canada’s total Black population. Quebec’s Black population has doubled in size in the past 20 years, with 325,000 people currently living here. This population is predominantly French speaking (80%), and it is concentrated in the Montreal metropolitan area (over 90%). The Black population tends to be younger than the Canadian average, and its members are more likely to be first-generation Canadians.
Parallel title: QUESCREN Working Paper no.4

Welcome to Whacky Wednesday - Montérégie West Community Network (MWCN) (2021)
Number of pages: 6

[Letter of Support re: Fulford Residence] - Celani, Paula; The English Speaking Catholic Council (ESCC) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 20

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2021)
Number of pages: 4

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 11

Y4Y Québec Holds Consultation to Explore Post-Secondary Students' Experiences During Pandemic : Youth Speak Up About Ongoing Challenges Throughout the COVID-19 Pandemic in Relation to their Mental Health and Educational Experience - Youth for Youth Québec (Y4Y Québec) (2021)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2021)
Number of pages: 1

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 18

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 9

EPCA Questions on Report Cards, Mask Policy : Insists on Simultaneous English Rollout - English Parents' Committee Association (EPCA) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 27

Harnessing your Transferable Skills in a COVID-19 Economy - Khamala, Maya (2021)

Job Search Mentorship During COVID-19 - Khamala, Maya (2021)

Skill-Building & Networking in the Time of COVID-19 - Khamala, Maya (2021)

Digital Outreach to Post-Secondary Students During Covid-19 - Lopes-Luchak, Milla (Youth for Youth Québec (Y4Y Québec), 2021)

Impact Report 2020-2021 - 4Korners (2021)

CHSSN Montreal Community Forum : Mental Health and COVID-19 - Community Health and Social Services Network (CHSSN) (2021)
The forum brought together representatives from the provincial government, the health sector, the community, various research initiatives, and leaders from across the Island of Montreal to discuss the effects of COVID-19 on mental health for English speakers living on the Island. The event also served as a platform forcelebrating the successes of different mental health initiatives and for co-generating solutions to some of the most urgent problems facing mental health amongst English speakers in the context of COVID-19. With the goal of deepening an understanding of the impact of COVID-19 on different demographic segments of the English-speaking population of Montreal, CHSSN invited speakers working with a wide range of populations and possessing diverse lived experiences of the pandemic. The forum was designed to foster cross-sectoral and intersectional exchanges and to create a space for learning, discovery, consciousness-raising, resource-sharing, networking, and collaborating.

Community NetLink - Community Health and Social Services Network (CHSSN) (2021)
Number of pages: 6

Community NetLink - Community Health and Social Services Network (CHSSN) (2021)
Number of pages: 10

The Newsletter - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 12

The Newsletter - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 17

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)
Number of pages: 28

Portrait of Men and Fathers in Quebec's English-Speaking Community & Their Relationship to Services - A Sociological View - Roy, Jacques (Community Health and Social Services Network (CHSSN), 2021)
What is the profile of English-speaking men in Quebec? Are they different from other Quebec men, mainly Francophones? Has the pandemic affected them more? Do they experience additional barriers to services imply because of their language? Finally, what policies and interventions could improve their condition and access to health and social services? These are the questions at the heart of this study. In order to shed light on these issues, the research uses an examination of recent survey results and public data to map out the English-speaking community in terms of the men and fathers who comprise it. Before doing so, a culturalist analytical framework is presented to better understand and interpret the results that emerge from the various sources of information used in the study. Finally, avenues for action in terms of public policy and intervention in practice settings are proposed to improve the situation of English-speaking men and fathers and to bring health and social services closer to their needs and reality. The results of surveys and public data reports form the basis for reflection on the actions to be taken.
Keywords: Official Language Minority Community (OLMC)

2020-2021 Annual Report - The English Speaking Catholic Council (ESCC) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2020)
Number of pages: 3

In celebration of Early Childhood Week, the Community Health and Social Services Network is pleased to present : Supporting the Well-being of Young Children in English-speaking Communities! - Community Health and Social Services Network (CHSSN) (2020)

QCGN Opposes Holding School Board Elections in Red Zones - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Forum for Youth Insights : Career and Education Orientations for the Post-COVID-19 World - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
The kids are (mostly) alright! That message was made loud and clear during a fascinating discussion when a group of passionate thinkers, educators, students, and speakers got together virtually on October 25, 2020, for Concordia University’s Forum for Youth Insights. An initiative of the Quebec English-Speaking Communities Research Network through its Inter-Level Educational Table, in collaboration with Youth 4 Youth Québec and the Black Community Resource Centre, this year’s forum had a special theme : Career and Education Orientations for the Post-COVID-19 World. In a nutshell, it was an opportunity for students to understand the new realities of the post-COVID-19 experience and how to navigate the sometimes confusing road ahead. Spoiler alert : We’re gonna be alright (but we need to recalibrate slightly).
Parallel title: Report : Key Insights and Takeaways

Forum for Youth Insights 2020 - Quebec English-speaking Communities Research Network (QUESCREN) (2020)

Call for Papers : The Impact of Black Lives Matter Movement in the Era of COVID-19 Pandemic - International Journal of Community Development & Management Studies (IJCDMS) (2020)

Annual Report 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

EPCA Welcomes New, Long Overdue, School Measures - English Parents' Committee Association (EPCA) (2020)

Supporting English Schools in Quebec Through the Pandemic - Advisory Board on English Education (2020)
The Advisory Board on English Education (ABEE) wrote to the Minister in June, 2020 regarding the return to school. Because little has changed since then among the concerns it raised, we urge the Minister to refer back to that document, included with this letter for your convenience. In September, ABEE met virtually to assess the situation in English-language schools and centres now that they are in operation after a six-month hiatus. In the words of one member, there were “different perspectives from different people with different responsibilities but all focused on how to play our part to make this work for our students, their families and our colleagues.” The discussion was wide-ranging, but several themes emerged that we respectfully share with the Minister.

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)
Number of pages: 2

Fall Colours Acoustic Concert - Cancelled Due to COVID-19 - Centre for Access to Services in English (CASE) (2020)

CAMI Newsletter - Council for Anglophone Magdalen Islanders (CAMI) (2020)
issued: March, 2020/September, 2020 Number of pages: 12

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 7

Back to School Plan : Working Together for a Serene and Safe Return to School - English Parents' Committee Association (EPCA); Quebec Federation of Parents’ Committees (FCPQ) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Neighbours Newsletter : August 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)
Number of pages: 12

Entrepreneurs and Artists in the Time of COVID-19 - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, Canadian governmental agencies and other organizations have deployed multiple programs to support local entrepreneurs and their businesses. In the current evolving situation, it’s hard to know where to turn. This document contains some of the currently available programs and resources for entrepreneurs and will be updated periodically. Last updated on July 27, 2020.

10 Innovative Projects to Assist Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2020)

Reisaction : Our Response to Covid-19 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)
Number of pages: 11

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

September Return to School : Parents Must Be Involved in Process - English Parents' Committee Association (EPCA) (2020)

Impact of Confinement on English-speaking Families - Community Health and Social Services Network (CHSSN) (2020)

Deconfinement Guidelines : What You Should Know in Times of Crisis - Seniors Action Quebec (SAQ) (2020)

Returning to School in the English Education System in Uncertain Times - Advisory Board on English Education (2020)
The sudden and widespread occurrence of COVID-19 has pointed out the great disparities across the province of Québec, such as the different situations between the cities and the regions, and also between sectors of the population within these settings. These differences have resulted in different policy decisions, such as when—or whether—to reopen schools, and we commend the Minister for applying local solutions to local situations. We hope this strategy will continue during the uncertainty that will apply to the probable second wave of the pandemic predicted for the Fall, and we welcome the possibility of different scenarios proposed in the working document on resumption of school for all in September. An unwelcome result of the rapidly changing situation and the need for quick decisions is the appearance of hasty, spontaneous decisions that are not conveyed appropriately to the educational partners who must respond to them. Policy -makers can react quickly. Systems can not. Announcing a policy then modifying or reversing it causes stress and confusion, especially when those who must implement the policy—including principals and teachers—feel excluded from the process.

COVID-19 Survey Report - Gaumond, Annie (Literacy Quebec, 2020)
On June 16, 2020, Literacy Quebec sent out an online survey to 11 member organizations. We asked about the needs and challenges of students, volunteers, and the organization, as well as the experience of working remotely during the COVID-19 pandemic. The survey closed on June 30, 2020 with a 100% response rate. We are pleased to share the summarized responses.

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Network News - Quebec Community Groups Network (QCGN) (2020)
Number of pages: 10

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 2

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 3

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 3

COVID-19 : Reopening of Schools : EPCA Survey to Parents - English Parents' Committee Association (EPCA) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 2

Jamaica Association of Montreal Newsletter : Special Edition: May 2020 : Volume 16.1 - Jamaica Association of Montreal (JAM) (2020)
Number of pages: 1

The QFHSA Back-to-School Survey : What Our Members Had To Say - Quebec Federation of Home and School Associations (QFHSA) (2020)
The Quebec Federation of Home and School Associations (QFHSA) surveyed its members recently on the Quebec government’s plan to reopen schools this spring. We learned that a small minority of parents (16.74%) plan to send their children back to school when it reopens. Of those who intend to keep their children at home, 65.5% are opting for distance learning; and 30%, home-schooling.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 6

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (2020)
Number of pages: 6

Gradual Reopening of Elementary Schools - English Parents' Committee Association (EPCA) (2020)

Reopening of Schools - English Parents' Committee Association (EPCA) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 3

QCGN Welcomes Wider Distribution of COVID-19 Self-care Guide to English Speaking Quebecers - Quebec Community Groups Network (QCGN) (2020)

Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

[Update to Parents Regarding School Reopenings] - English Parents' Committee Association (EPCA) (2020)

Seniors Action Quebec Statement on Situation at Residence Herron - Seniors Action Quebec (SAQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 4

The English-speaking Community of the Magdalen Islands Takes Action to Mitigate the Effects of the COVID-19 Pandemic - Council for Anglophone Magdalen Islanders (CAMI) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 4

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 2

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Neighbours Newsletter : April 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)
Number of pages: 12

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 3

FAQ Regarding the Canadian Emergency Response Benefit (CERB) Program - McSween, Pierre-Yves (2020)
Disclaimer: This document has been prepared with the information in public circulation as of March 26, 2020. This is not an official communication from the government and information presented here is not to be used as proof of eligibility. YES has translated and edited the original text for clarity. This information is provided solely as a resource. As this is an evolving document, the user of this information is responsible for determining and verifying the accuracy of the data presented here and how it is used.

Partners in Health - Centre for Access to Services in English (CASE) (2020)
Number of pages: 3

Network News - Quebec Community Groups Network (QCGN) (2020)
Number of pages: 3

Impact Report 2019-2020 - 4Korners (2020)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)
Number of pages: 14
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)
Number of pages: 15

Enhancing Regional Capacity / Reforcer la capitacité communautaire régionale - Community Health and Social Services Network (CHSSN) (2020)
Number of pages: 10

Adapting Services During the Pandemic : The Example of Jeffery Hale-Saint Brigid's and Its Partners - Duchesne, Anne (2020)

[Update to Parents Regarding Return to School for Fall 2020] - English Parents' Committee Association (EPCA) (2020)

Jackie Robinson Golf Tournament - Gunning, Glen; Piggot, Sylvia (BASF) (2020)

An Uncertain Future for the Future of Québec : Policy Brief on the Under Employment of English-speaking Youth in the Quebec Civil Service - Lawler, Madeleine (Youth for Youth Québec (Y4Y Québec), 2020)
Since the start of the COVID-19 global pandemic, post-secondary students have been amongst the hardest hit economically. In the span of two months, the unemployment rate amongst Canadian post-secondary students almost doubled, and less than a quarter of previously employed students continued working their regular hours. The global pandemic further exacerbated pre-existing issues of economic vulnerability and underemployment amongst English-speaking youth in Quebec. According to a 2018 CHSSN report, the unemployment rate amongst English-speaking youth was 13.3%, whereas that of their Frenchspeaking counterparts was 9.8%.2 Across different industries, the under-employment of Englishspeaking youth is perhaps the most pitiful within the Quebec civil service. In general, anglophones have represented between 0.7% and 1% of the provincial civil service for nearly half a century, despite representing 7.4% of the population in 2016

Communications During COVID Time - NDG Community Council (NDGCC) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)
Number of pages: 28

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)
Number of pages: 28

Covid-19 : Considerations When Deciding to Move Seniors from Residences or CHSLDS - Seniors Action Quebec (SAQ) (2020)

Tips on Helping Seniors Deal with Isolation During Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

What to Ask a Senior's Residence During the Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

2019-2020 Annual Report - The English Speaking Catholic Council (ESCC) (2020)

Small Business Resource Guide - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, we have compiled a resource guide for small businesses to help you navigate these challenging times.

In Survival Mode : Adult Education Teachers Experience of Covid-19 and their Use of Digital Technologies - Bowles, Emilie

Evolution of Psychosocial Impacts During the 2nd Wave of the COVID-19 Pandemic : A Quebec Study - Généreux, Mélissa